Governing Finance in Europe: A Centralisation of Rulemaking? - Magnus G. Schoeller (Edward Elgar Publishing, 2020)
How do regulatory structures evolve in EU financial governance? Incorporating insights from a variety of disciplines, Governing Finance in Europe provides a comprehensive framework to investigate the dynamics leading to centralisation, decentralisation and fragmentation in EU financial regulation.